2009
DOI: 10.1016/j.jce.2008.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Labor regulation and employment in India's retail stores

Abstract: JEL classification: J080 K31 L81 O53 Keywords: Labor regulations India Employment Retail Informality Amin, Mohammad-Labor regulation and employment in India's retail storesA new dataset of 1948 retail stores in India shows that 27% of the stores find labor regulations as a problem for their business. Using these data, we analyze the effect of labor regulations on employment at the store level. We find that flexible labor regulations have a strong positive effect on job creation. Our estimates show that labor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 12 publications
1
27
0
2
Order By: Relevance
“…Businesses clamored loudly that the Law would reduce employment and competitiveness. This view is supported by a majority of previous microeconomic studies on the impact of labor regulations on employment in developing countries which find that labor regulations reduce employment and increase unemployment (Besley and Burgess, 2004;Ahsan and Pages, 2009;Fledmann, 2009;Djankov and Ramalho, 2009;Kaplan, 2009;Amin, 2007;Fallon and Lucas, 1993). Other authors have found that strict enforcement of labor regulations raises the costs of formal employment, and thus leads to greater informal employment (Almeido and Carneiro, 2005).…”
mentioning
confidence: 89%
“…Businesses clamored loudly that the Law would reduce employment and competitiveness. This view is supported by a majority of previous microeconomic studies on the impact of labor regulations on employment in developing countries which find that labor regulations reduce employment and increase unemployment (Besley and Burgess, 2004;Ahsan and Pages, 2009;Fledmann, 2009;Djankov and Ramalho, 2009;Kaplan, 2009;Amin, 2007;Fallon and Lucas, 1993). Other authors have found that strict enforcement of labor regulations raises the costs of formal employment, and thus leads to greater informal employment (Almeido and Carneiro, 2005).…”
mentioning
confidence: 89%
“…Amin (2007) em uma pesquisa realizada com 1.948 lojas de varejo na Índia mostraram que 27% das lojas relataram que as leis trabalhistas são um problema para o desenvolvimento dos seus negócios. Os achados desta pesquisa mostraram que uma regulação mais estrita do trabalho tem um forte efeito negativo sobre o emprego.…”
Section: Regulação Do Trabalhounclassified
“…and Pages, 2007;Amin, 2008;Almeida and Carneiro, 2009). 16 A possible associated effect is that workers who lose their jobs may offer their hours of work in the informal sector depending on workers' valuation of the mandated benefits being enforced (Almeida and Carneiro, 2012;.…”
Section: Theoretical Channelsmentioning
confidence: 99%